GROWTH AND SURVIVAL RATE OF FISH (Channa micropeltes) FED Tubifex sp WITH DIFFERENT AMOUNTS - Candra, Andre Maryan; Putra, Iskandar; Rusliadi, Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in Desember 2017 to January 2018 in the Aquatic Aquaculture Technology Laboratory of Marine Fishery University of Riau. The aims of this determine was to growth and survival rate of Channa micropeltes fed Tubifex sp with different amounts. This research used a size aquarium 40 x 30 x 40 cm3 with a water height 10 cm for 12 units. The feed used in the form of Tubifex sp, given with dose of 5, 10, 15 and 20% from the body weight of the fish. The method used in this research was the experimental method of Completely Randomized Design (CRD) using one factor with 4 treatments and 3 replications. The best treatment result is feeding with dose 20% body weight which can produce absolute weight growth rate (5,25 gram), absolute length growth (3,61 cm), growth of specific length (1,46%) and survival rate (86.67%). Water quality during the research was obtained pH 6.0-7.0, temperature 26-28 0C, DO 3,1-3,2 mg / L. These result of research growth and survival of Channa micropeltes fed Tubifex sp with different amounts gives a significant effect on the growth rate and survival Channa micropeltes. Keywords : Tubifex sp, Channa micropeltes, Growth and survival rate.